Bacterial Meningitis in Infants Under 90 Days of Age: A Retrospective Single-Center Study - Martina Buttera; Sofia Mazzotti; Tommaso Zini; Lucia Corso; Valeria Dallai; Francesca Miselli; Luca Bedetti; Katia Rossi; Eugenio Spaggiari; Lorenzo Iughetti; Licia Lugli; Alberto Berardi (Children)
Background: Bacterial meningitis (BM) in infants is a serious condition that can lead to significant complications. Lumbar puncture (LP) is essential to provide diagnoses, however false negatives may result if LP is performed after the starting of antibiotic therapy. Methods: We conducted a retrospective analysis of infants of any gestational age with BM within their first 90 days of life and admitted to the Neonatal Intensive Care Unit of Modena Policlinico between 1 January 2011, and 31 December 2023. Results: A total of 44 episodes of meningitis were confirmed in 40 infants, diagnosed by positive cerebrospinal fluid cultures (n = 37), polymerase chain reaction testing (n = 4), or both methods (n = 3). Three out of forty infants (8%) experienced a relapse of meningitis. Most episodes (31/44, 70%) occurred in preterm infants. The incidence of early-onset meningitis was lower than that of late-onset (0.18 vs. 0.94 cases per 1000 births, respectively), with Gram-positive accounting for most cases (27/44, 61%). LP was performed prior to antibiotic administration in most episodes (30/44, 68%). Two preterm infants (5%) died from meningitis-related complications. Forty-two episodes occurred among thirty-eight surviving infants; brain lesions were detected through brain ultrasound or MRI in nine out of forty-two episodes (21%). Conclusions: Preterm infants have higher rates of BM, brain lesions or case fatalities. Early diagnosis and prompt antibiotic treatment are critical to improve outcomes.